Structure, diversity, and spatial patterns in a permanent plot of a high Restinga forest in Southeastern Brazil - Lima, Renato Augusto Ferreira De; Oliveira, Alexandre Adalardo De; Martini, Adriana Maria Zanforlin; Sampaio, Daniela; Souza, Vinícius Castro; Rodrigues, Ricardo Ribeiro (Sociedade Botânica do Brasil, 2011)
We assessed the structure, diversity and distribution of tree species in a 10.24-ha permanent plot of high Restinga forest (HRF) in southeastern Brazil. We sampled 15,040 individuals belonging to 45 families, 87 genera and 116 species (density= 1,468 trees ha-1, and basal area= 28.0 m² ha-1). Mean richness was lower than other types of tropical forests and other HRFs that have been less intensively sampled, which is probably due to the younger age and hydromorphy of the soils in the study site. Tree density, basal area, species composition, and diversity all varied considerably depending on the size class considered. The studied plot had a density similar to other tropical forests but with a smaller basal area (fewer individuals > 60 cm in diameter), and higher density of smaller trees. Multi-stemmed individuals were not frequent (11% of the trees), though they were widespread among species (74% of the species). Spatial distribution was predominantly clumped, a pattern common to other types of tropical forests. Besides growing over white-sand soils, the PEIC plot and other white-sand forests of the world also had very similar patterns of community structure, richness and diversity. Therefore, we consider the HRF as a recognizable subtype of white-sand forest.

Nós investigamos a estrutura, diversidade e distribuição de espécies arbóreas em uma parcela de 10,24 ha de uma floresta alta de Restinga (FAR) no Sudeste do Brasil. Nós amostramos 15.040 indivíduos pertencentes a 45 famílias, 87 gêneros e 116 espécies (densidade= 1.468 árvores ha-1, e área basal= 28,0 m² ha-1). A riqueza média foi menor que outros tipos de florestas tropicais e outras FAR amostradas em menor intensidade, provavelmente pela juventude e hidromorfia dos solos na área de estudo. A densidade, área basal, composição e diversidade arbórea variaram consideravelmente de acordo com a classe de tamanho considerada. A parcela estudada teve uma densidade similar a outras florestas tropicais, mas com menor área basal (menos indivíduos > 60 cm de diâmetro) e maior densidade de árvores pequenas. Fustes múltiplos não foram frequentes (11% dos indivíduos), mas foram comuns entre as espécies (74% das espécies). A distribuição espacial foi predominantemente agregada, um padrão comum a outros tipos de florestas tropicais. Além do substrato arenoso, a parcela estudada e outras florestas de areia branca do mundo tiveram padrões muito similares de estrutura, riqueza e diversidade. Assim, consideramos a FAR como um subtipo evidente de floresta de areia branca.
Estrutura, diversidade e padrões espaciais em uma parcela permanente de floresta alta de Restinga no Sudeste do Brasil
Keywords: classes de tamanho de árvores; Floresta Atlântica; fustes múltiplos; riqueza de espécies; Atlantic Forest; multi-stemmed trees; species richness; tree size classes